ARTICULATORY AND ACOUSTICS CHARACTERISTICS OF SPEECH SOUNDS: THE ROLE OF SPEECH ORGANS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of the articulatory and acoustic features of speech sounds, focusing on the critical role of speech organs in the production of these sounds. It delves into the fundamental concepts of articulatory phonetics, including the place and manner of articulation, as well as the concept of voicing, which are essential for understanding how different sounds are produced in the vocal tract. Additionally, the article explores the key acoustic features such as frequency, amplitude, formants, and voice onset time (VOT), which define the physical properties of speech sounds as they travel through the air. It also highlights the function of various speech organs, distinguishing between active articulators (such as the tongue and lips) and passive articulators (like the teeth and alveolar ridge). Overall, the article bridges the study of sound production and its acoustic characteristics, offering a holistic view of how humans produce and perceive speech. This serves as a foundational resource for anyone interested in phonetics, linguistics, or speech science.